Skrining Kemampuan Phonological Awareness Anak Pra Sekolah - Arif Siswanto; Hafidz Triantoro Aji Pratomo (Poltekkes Kemenkes Surakarta, 2019)
Background. In the learning process at school, especially in pre-school education, phonological ability is the entrance for children in mastery of language. In Indonesia, research that focuses on phonological abilities in pre-school children is still very limited. Objective. This study aims to determine the profile of pre-school children's phonological awareness abilities. Method. Participants were recruited from the Surakarta ABA Thoyibah Kindergarten with a total of 27 class B children to participate in this study. Screening is given to participants. The screening results will reflect the profile of children's phonological awareness abilities. Results. There are five items that can be used to screen pre-school children's phonological awareness skills: rhyme, syllable blending, initial phoneme identification, medial phoneme identification, and final phoneme identification. The results of the internal validation analysis of phonological awareness subtest were as follows: rhyme 0.684, syllable blending 0.772, initial phoneme identification 0.880, medial phoneme identification 0.862, and final phoneme identification 0.735. Conclusion. The value of internal validity or the correlation between items in phonological awareness screening is good because all items correlated have a correlation with a low probability value.